Private London - Patterson, James 1947-; Pearson, Mark 1960-; Degas, Rupert (New York : Hachette Audio, 2011)
Dan Carter, head of the London division of Private, the world's most exclusive detective agency, must join forces with his ex-wife if he is going to save American student Hannah Shapiro from a threat that has stalked her for eight years.
Unabridged.
Compact discs.
Read by Rupert Degas.
Keywords: Private security services -- Fiction; Private investigators -- Fiction -- England; Suspense fiction; Audiobooks